Modelling basin-scale CO2 storage in the Bunter Sandstone of the UK Southern North Sea - Agada,S; Kolster,C; Williams,G; Krevor,S (2016)
In this paper, a reservoir simulation model of the large-scale Bunter Sandstone in the UK Southern North Sea is used to evaluate the dynamics of regional CO2 plume transport and storage. We have tested the sensitivity of injection capacity to a range of target CO2 injection rates and the number of sites at which injection is deployed. In addition to geology, the model is constrained by local bottom-hole-pressure (BHP) limits and site spacing. Large-scale pressure buildup limitations and the impact of brine production on storage capacity are also evaluated. Furthermore, monitoring of the CO2 plume at multiple injection sites indicates important subsurface controls on plume migration in the context of short-term (approx. 50 years) and long-term CO2 storage (approx. 1000 years).